2019
DOI: 10.1182/bloodadvances.2018025114
|View full text |Cite
|
Sign up to set email alerts
|

Progression of mycosis fungoides occurs through divergence of tumor immunophenotype by differential expression of HLA-DR

Abstract: Immunotherapy is a valuable treatment for many cancer patients, and there is considerable interest in understanding the mechanisms of immune evasion to guide appropriate management. Mycosis fungoides (MF) is a malignant disorder of skin-homing CD4+ T cells, and it exhibits a highly variable clinical course during which the tumor-specific immune response may be an important determinant. An unusual feature of MF is that tumor-infiltrating lymphocytes (TILs) must attempt to control a malignant cell from within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 34 publications
1
21
1
1
Order By: Relevance
“…Ki-67 proliferation indices increase as the disease progresses, with tumor stage evolution or transformation to larger cells and may correlate with prognosis (Edinger, Clark, Pucevich, Geskin, & Swerdlow, 2009;Raghavan, Hong, Kim, & Kim, 2019). CD25 can also be identi- Although not routinely used at this time, FC of skin specimens may be able to distinguish between tumor cell and tumor infiltrating lymphocyte "immune escape" phenotypes using clonotypic TCR-Vβ staining and activation/exhaustion markers such as PD-1 and programmed death receptor ligand-1 (PD-L1), with the potential for eventual therapeutic stratification (Murray et al, 2019). FC has identified both small and large cell shared monoclonal populations in MF not seen by immunohistochemistry, with CD3+/CD26− T cells accounting for 70% of MF cases, and absent CD7 only in 57% of cases.…”
Section: Immunophenotyping Of Mf Cells In Skinmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki-67 proliferation indices increase as the disease progresses, with tumor stage evolution or transformation to larger cells and may correlate with prognosis (Edinger, Clark, Pucevich, Geskin, & Swerdlow, 2009;Raghavan, Hong, Kim, & Kim, 2019). CD25 can also be identi- Although not routinely used at this time, FC of skin specimens may be able to distinguish between tumor cell and tumor infiltrating lymphocyte "immune escape" phenotypes using clonotypic TCR-Vβ staining and activation/exhaustion markers such as PD-1 and programmed death receptor ligand-1 (PD-L1), with the potential for eventual therapeutic stratification (Murray et al, 2019). FC has identified both small and large cell shared monoclonal populations in MF not seen by immunohistochemistry, with CD3+/CD26− T cells accounting for 70% of MF cases, and absent CD7 only in 57% of cases.…”
Section: Immunophenotyping Of Mf Cells In Skinmentioning
confidence: 99%
“…FC analysis of lymphocytes from mechanically extracted and digested skin biopsy specimens has shown diagnostic T‐cell aberrancies in patients with clinical and histologic findings consistent with MF, and not with indeterminate or negative findings (Jokinen et al, 2011; Oshtory, Apisarnthanarax, Gilliam, Cooper, & Meyerson, 2007). Although not routinely used at this time, FC of skin specimens may be able to distinguish between tumor cell and tumor infiltrating lymphocyte “immune escape” phenotypes using clonotypic TCR‐Vβ staining and activation/exhaustion markers such as PD‐1 and programmed death receptor ligand‐1 (PD‐L1), with the potential for eventual therapeutic stratification (Murray et al, 2019). FC has identified both small and large cell shared monoclonal populations in MF not seen by immunohistochemistry, with CD3+/CD26− T cells accounting for 70% of MF cases, and absent CD7 only in 57% of cases.…”
Section: Diagnosis Of Mf and Ss: Role Of Immunophenotypingmentioning
confidence: 99%
“…However, it has been shown that CD8+ T-cells are unable to exert an effective cytotoxic action, resulting in immune tolerance against the malignant CD4+ T-cells [15]. Specifically, TILs in MF patients exhibit an exhausted phenotype, which is characterized by the upregulation of various co-inhibitory receptors such as PD-1 (program death 1, encoded by PDCD1) and TIM-3 (T cell immunoglobulin and mucin domain-containing protein 3, encoded by HAVCR2/TIM-3) [99]. Transient upregulation of co-inhibitory receptors on T-cells can serve as a homeostatic mechanism to maintain self-tolerance and prevent excessive immune response [100].…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…However, one study showed an upregulation of HAVCR2 and PDCD1 from isolated CD8+ T-cells of MF lesions, which suggests that these co-inhibitory genes are predominantly associated with the non-malignant T-cells [15]. However, it is also known that MF cells frequently express PD-1 [99]. Specifically, the interaction of PD-1 with its ligand, PD-L1/L2, transduces a negative signal that inhibits T-cell proliferation and cytotoxicity, impeding effective anti-tumor response [102].…”
Section: Immune Checkpointsmentioning
confidence: 99%
“…Σε πρόσφατη μελέτη από τους Murray et al, βρέθηκε ότι η IL-17 παράγεται από τα κακοήθη λεμφοκύτταρα του δέρματος στη σπογγοειδή μυκητίαση, αλλά κι από ένα ποσοστό φυσιολογικών Τ-λεμφοκυττάρων που διηθούν τις δερματικές βλάβες και βοηθούν στην άμυνα του οργανισμού (TILs: Tumor infiltrating cells). Επίσης παρατηρήθηκε ότι η έκφραση της IL-17 ήταν αυξημένη ιδίως στα αρχικά στάδια της νόσου και μειωνόταν σε πιο προχωρημένα στάδιά της 74 .…”
Section: η ε π ι δ ρ α σ η τ ω ν I L -1 7 a I L -1 7 F κ α ι I L -2 2 σ τ O δ ε ρ μ αunclassified